Annual report to the government of Antigua Barbuda 1990 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2021)
Actions of the institute are presented by the representation of Antigua Barbuda, during 1990, such as agricultural policies, technology transfer, organization and management for rural development, marketing in agribusiness, health and agricultural protection, in addition to some national and multinational projects in favor of these areas.